A coordinated microstructural and isotopic study of a Wark-Lovering rim on a Vigarano CAI. (15th January 2020) - Han, Jangmi; Keller, Lindsay P.; Liu, Ming-Chang; Needham, Andrew W.; Hertwig, Andreas T.; Messenger, Scott; Simon, Justin I.
Abstract: We carried out a coordinated mineralogical and isotopic study of a Wark-Lovering (WL) rim on a Ca, Al-rich inclusion (CAI) from the reduced CV3 chondrite Vigarano. The outermost edge of the CAI mantle is mineralogically and texturally distinct compared to the underlying mantle that is composed of coarse, zoned melilite (Åk∼10-60 ) grains. The mantle edge contains fine-grained gehlenite with hibonite and rare grossite that likely formed by rapid crystallization from a melt enriched in Ca and Al. These gehlenite and hibonite layers are surrounded by successive layers of spinel, zoned melilite (Åk∼0-10 ), zoned diopside that grades outwards from Al, Ti-rich to Al, Ti-poor, and forsteritic olivine intergrown with diopside. These layered textures are indicative of sequential condensation of spinel, melilite, diopside, and forsterite onto hibonite. Anorthite occurs as a discontinuous layer that corrodes adjacent melilite and Al-diopside, and appears to have replaced them, probably even later than the forsterite layer formation. Based on these observations, we conclude that the WL rim formation was initiated by flash melting and extensive evaporation of the original inclusion edge, followed by subsequent gas-solid reactions under highly dynamic conditions. All the WL rim minerals are 16 O-rich (Δ 17 O = ∼−23‰), indicating their formation in an 16 O-rich nebular reservoir. Our Al-Mg measurements of hibonite, spinel, and diopside from the WL rim, as well as spinel and Al, Ti-diopside in the core, define a single, well-correlated isochron with an inferred initial 26 Al/ 27 Al ratio of (4.94 ± 0.12) × 10 −5 . This indicates that the WL rim formed shortly after the host CAI. In contrast, the lack of 26 Mg excesses in the WL rim anorthite suggest its later formation or later isotopic disturbance in the solar nebula, after 26 Al had decayed.